Performance-threshold-based resilience analysis of system of systems by considering dynamic reconfiguration. (December 2022) - Chen, Zhiwei; Zhao, Tingdi; Jiao, Jian; Chu, Jiayun
In recent years, system of systems resilience has been widely studied. System of systems has obvious resilience properties when considering dynamic reconfiguration in the following four parts: avoidance, survival, adaption and recovery. System of systems can be downgraded and recovered by reconfiguring resources to keep the performance output enough to satisfy the threshold under internal failure or external shocks. In other words, because of dynamic reconfiguration, system of systems has obvious characteristics of resilience. In this study, first, a new resilience model for systems and system of systems based on the performance threshold is proposed. Second, military system of systems is decomposed hierarchically, including system of systems–level, platform-level and system-level top-down, respectively. Third, a radar network of military system of systems is taken as a typical case. A performance model for a radar network under internal or external shocks is established based on the linear-Gauss-Poisson process in system of systems, and its parameters are discussed in detail. Finally, a typical 5-node radar network of formation air defense military system of systems is taken as an example to demonstrate proposed models and methods. The reliability and resilience loss are achieved by considering internal failure or external shocks, which can serve as a reference for evaluating and improving the effectiveness of system of systems.